Calidad del servicio de atención al contribuyente y su influencia en la decisión de pago voluntario del usuario, en el área de cobranza coactiva de la Intendencia Regional La Libertad, SUNAT - Trujillo 2016. - Ramirez Alva, Cristina Rosybel (2016)
This research was developed in order to determine to what extent the quality of taxpayer service influences the decision of voluntary payment of the user, in the area of enforced collection of regional quartermaster La Libertad, SUNAT -Trujillo 2016. It has been used as a population to calculate the sample medium and small taxpayers of the Regional Municipality La Libertad - Trujillo SUNAT given limited access to information. Within this research analyzed aspects such as: the level of satisfaction of taxpayers of the Regional Municipality of La Libertad with the service received by the area of enforced collection of such dependence; the level of tax culture thereof; the level of propensity to payment; more types made embargoes; the quality of taxpayer service in the area of enforced collection; the main reasons for the tax debt and the level of confidence in the institution. The following hypothesis is proposed: The quality of taxpayer service greatly influences the decision of voluntary payment of the user, in the area of enforced collection of regional quartermaster La Libertad, SUNAT -Trujillo 2016. This was used the deductive analysis - synthesis, hypothetical - deductive inductive methods, and hermeneutical; a design no experimental research; and technical data collection survey. Completed the process of investigation is concluded that the hypothesis is accepted, as well as results for the aspects analyzed are determined. Finally some recommendations to improve service and promote voluntary compliance with tax obligations are plotted.